The Impact of Price Perceptions, Social Media Marketing and Brand Image on Purchasing Decisions of Pink Flash Cosmetics Makeup Products - Erly Herlynda, Berliana; Pramudita, Rezki Aulia (IQTISHADequity jurnal MANAJEMEN, 2024)
This study aims to analyze the influence of price perception, social media marketing and brand image on purchasing decisions on Pink Flash brand cosmetic makeup products. Pink Flash is a brand from China that is engaged in makeup and skincare with a price benchmark that is considered quite affordable. This study is quantitative research with a multiple regression analysis method where the data collection technique is by questionnaire method, data analysis software in this study uses SPSS 25 program tools. The results of the study were: (1) price perception had a positive and significant effect on purchase decisions (Sig = 0.004 < 0.05; ? 0.474). (2) social media marketing has a positive and significant effect on purchasing decisions (Sig = 0.000 < 0.05; ? 0.611). (3) brand image has a positive and significant effect on purchase decisions (Sig = 0.000 < 0.05; ? 0.745). Meanwhile, the simultaneous influence of price perception, social media marketing and brand image on purchase decisions was 0.524. Which means that all X variables in this study have an effect of 52.4% on purchase decisions and the remaining 47.6% are influenced by other variables that are not studied.